HISTORY OF DIAGNOSTIC CYTOLOGY - Albújar, Pedro (2015)
You can define the Diagnostic Cytology as the art and science that deals with the morphological interpretation of human cells, are exfoliated or obtained by other methods. Its two main cambos clinical application are cytodiagnosis cancer and hormone cytology.